Enrichment of Fermented Milk Drinks with Mespilus germanica and Crataegus azarolus Fruit Extracts - Papademas, Photis; Ioannou, Ioanna; Aspri, Maria (My University, 2023)
The aim of the present study was to select the optimal extraction conditions for two underutilized wild fruits of the Rosaceae family (Mespilus germanica and Crataegus azarolus) in order to investigate the possibility of utilizing their potential bioactive properties by developing novel fermented milk drinks enriched with fruit extracts, with functional properties. The total phenolic and flavonoid contents of the extracts, as well as their antioxidant and antidiabetic activities, were evaluated, and based on the results, the optimal extraction conditions were selected. The technological characteristics (i.e., fermentation conditions) and microbiological and bioactive properties of the final products were evaluated over refrigerated storage for 28 days. The findings of the study showed that the incorporation of Mespilus germanica or Crataegus azarolus extracts had a positive influence on the bioactive properties of the end-products, decreased fermentation times and maintained high viable populations of lactic acid bacteria. Hence, it can be concluded that Mespilus germanica or Crataegus azarolus extracts can be exploited in the enrichment of an added-value fermented milk drink.
Keywords: antidiabetic; antioxidant activity; bioactive fermented milk drink; Crataegus azarolus; Mespilus germanica; phenolic compounds